The "unnatural" history of colorectal cancer in Lynch syndrome: Lessons from colonoscopy surveillance. Issue 4 (3rd August 2020) - Ahadova, Aysel; Seppälä, Toni T.; Engel, Christoph; Gallon, Richard; Burn, John; Holinski‐Feder, Elke; Steinke‐Lange, Verena; Möslein, Gabriela; Nielsen, Maartje; ten Broeke, Sanne W.; Laghi, Luigi; Dominguez‐Valentin, Mev; et al.
Abstract: Individuals with Lynch syndrome (LS), one of the most common inherited cancer syndromes, are at increased risk of developing malignancies, in particular colorectal cancer (CRC). Regular colonoscopy with polypectomy is recommended to reduce CRC risk in LS individuals. However, recent independent studies demonstrated that a substantial proportion of LS individuals develop CRC despite regular colonoscopy. The reasons for this surprising observation confirmed by large prospective studies are a matter of debate. In this review, we collect existing evidence from clinical, epidemiological and molecular studies and interpret them with regard to the origins and progression of LS‐associated CRC. Alongside with hypotheses addressing colonoscopy quality and pace of progression from adenoma to cancer, we discuss the role of alternative precursors and immune system in LS‐associated CRC. We also identify gaps in current knowledge and make suggestions for future studies aiming at improved CRC prevention for LS individuals.